2023
DOI: 10.30935/ijpdll/13191
|View full text |Cite
|
Sign up to set email alerts
|

Assessing elementary understanding of electromagnetic radiation and its implementation in wireless technologies among pre-service teachers

Abstract: The research on the knowledge and perceptions of electromagnetic radiation among teachers who will teach these topics in primary and secondary education is relatively limited. According to existing literature, electromagnetic radiation is a challenging and complex concept for students to comprehend. Despite the widespread use of radiation-emitting devices like cell phones and wireless networks, the misuse of the term “radiation” has resulted in various misconceptions. This study aimed to examine the elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
2
4
0
Order By: Relevance
“…Another observation, evident from the demographic data of the research, is that female educators significantly outnumber their male counterparts, a trend also documented in other studies (OECD, 2018;Ohide & Mbogo, 2017). The societal environment and prevailing expectations regarding women's involvement in STEM fields remain notably restrained, subtly nudging them toward alternative scientific domains like Theoretical Sciences and lower-tiered education (Gavrilas & Kotsis, 2023). It appears that girls tend to demonstrate more interest, engagement, and accumulation of experience and knowledge in areas such as cooking, caregiving, and arts, aligning with longstanding societal stereotypes (Gavrilas et al, 2020a(Gavrilas et al, , 2022Gontas et al, 2020;Tindall & Hamil, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…Another observation, evident from the demographic data of the research, is that female educators significantly outnumber their male counterparts, a trend also documented in other studies (OECD, 2018;Ohide & Mbogo, 2017). The societal environment and prevailing expectations regarding women's involvement in STEM fields remain notably restrained, subtly nudging them toward alternative scientific domains like Theoretical Sciences and lower-tiered education (Gavrilas & Kotsis, 2023). It appears that girls tend to demonstrate more interest, engagement, and accumulation of experience and knowledge in areas such as cooking, caregiving, and arts, aligning with longstanding societal stereotypes (Gavrilas et al, 2020a(Gavrilas et al, , 2022Gontas et al, 2020;Tindall & Hamil, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…Unfortunately, have been reported that students and primary education teachers have the same misconceptions about science concepts and phenomena (Kotsis, 2023). The same has been reported for the Pre-service teachers (Gavrilas & Kotsis, (2023); Stylos et al, 2023), making the problem very important. Under these circumstances, the teacher cannot use the proposed methods to change the students' misconceptions since he has the same perceptions as his students.…”
Section: Teachers and Students Have The Same Misconceptionsmentioning
confidence: 84%
“…Some students may view science as boring or irrelevant, while others may negatively perceive their ability to succeed in science. Even gender plays a crucial role in perceptions of physics (Reid & Skryabina, 2003;Gavrilas et al, 2023). Moreover, students with negative attitudes towards science are less likely to pursue science-related careers in the future.…”
Section: Student Attitudes and Perceptionsmentioning
confidence: 99%
“…For the effective education of students in the development of environmental awareness, educators play a significant role (Gavrilas & Kotsis, 2023a;Tuncer et al, 2009). Educators should possess the appropriate knowledge and a friendly attitude toward the environment to teach and sensitize their students (Gontas et al, 2020;Oncu & Unluer, 2015;Papanikolaou et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%